"Market Supervisor/Inspector" and "Public Moral Officer" as Translations of the Term Muhtasib: An Evaluation of Their Appropriateness - ASM Shahabuddin, Sabri Orman (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
"Market Supervisor/Inspector" and "Public Moral Officer" as Translations of the Term Muhtasib: An Evaluation of Their Appropriateness